Performance, Emissions, and Combustion Analysis of Gasoline-Ethanol-Methanol Blends in a Spark-Ignition Engine - Mokhtar; Danardono Agus Sumarsono; Askar Adika Agama; Ade Kurniawan; Hari Setiapraja (Results in Engineering)
The 125 cm3, four-stroke, air-cooled, electronic fuel injection SI engine for motorcycles was used to compare the effects of mixing methanol and ethanol with gasoline on engine power, fuel efficiency, and engine emissions. The tests were conducted on a dynamometer at various engine speeds under wide-open throttle conditions. The fuel variations included three ternary fuel blends and two binary fuel blends, each comprising 80% gasoline and varying ratios of methanol and ethanol by volume. Among the tested blends, the formulation containing 10% methanol and 10% ethanol (M10E10) demonstrated the greatest improvement in engine performance, with power and torque increasing by 2.4% and 0.4%, respectively, compared to pure gasoline. However, M10E10 also exhibited higher fuel consumption, with a 10.89% increase in brake specific fuel consumption (BSFC) compared to gasoline. Exhaust gas emissions showed that the ternary fuel blends resulted in lower exhaust gas emissions compared to gasoline, with average reductions in carbon monoxide (CO), nitrogen oxides (NOx), and total hydrocarbons (THC) exceeding 20%, 10%, and 10%, respectively. Nevertheless, carbon dioxide (CO₂) emissions were, on average, 5% higher for the alcohol blended fuels. Combustion analysis indicated that gasoline-ethanol-methanol blends enhanced the coefficient of variation of indicated mean effective pressure and improved the heat release characteristics. This study demonstrates that the use of ternary gasoline-ethanol-methanol blends in an unmodified motorcycle engine can lead to improved performance, reduced emissions, and enhanced combustion characteristics under certain conditions. However, further optimization of the fuel blend ratios and engine parameters is necessary to achieve the best balance of performance, emissions, and combustion efficiency.